Geochemistry of sediments in three sectors of Trincomalee Bay, Sri Lanka: provenance, modifying factors and present environmental status - Young, Sansfica M.; Ishiga, Hiroaki; Roser, Barry P.; Pitawala, Amarasooriya (Springer-Verlag Berlin Heidelberg, 2013)
Purpose The geochemical compositions of sediments from three sectors in Trincomalee Bay (Koddiyar Bay, Thambalagam Bay and the Inner Harbour) in Sri Lanka were examined to determine fluvial and marine contributions and the effects of sorting and heavy mineral concentration. The present environmental status of the bay was also assessed. Materials and methods Forty-nine sediment samples were collected from Trincomalee Bay and analysed by X-ray fluorescence, yielding data for the major elements and 17 trace elements. Mean grain size and sorting were also measured. Data were compared with the compositions of sediments from the lower Mahaweli River, which supplies most of the clastic detritus to Trincomalee Bay. Results and discussion Sediments in the three sectors differ significantly in chemical composition, according to position relative to the Mahaweli River delta source, depositional envi ronment, heavy mineral concentration and marine influences. According to accepted sediment quality guidelines, some As contamination may have occurred in the Inner Harbour and Thambalagam Bay and Cr contamination in all three sectors. Conclusions Proximal Koddiyar Bay sediments compare closely with Mahaweli River bedload. Although the clastic component in the more distal Thambalagam Bay and the Inner Harbour is also derived from the Mahaweli River, compositions are modified significantly by marine contributions. High concentrations of elements including Ti, Zr, Ce, Nb and Y in NW Koddiyar Bay are consistent with heavy mineral concentration by winnowing in high-energy zones. Some decoupling of Fe–Ti- and Zr-bearing heavy mineral assemblages may occur within the bay. Al-normalized metal enrichment factors and contour maps show that apparent contamination by As and Cr is spurious and is caused by locally high background levels from Mahaweli River detritus. This illustrates the importance of establishing local background levels of elements during environmental studies.
Keywords: Geochemistry; Pollution; Sediments; Provenance; Sri Lanka; Trincomalee Bay